Inhibition of Staphylococcus aureus by Nigella sativa products using different extraction method - Saleh, Faraydoon AK.; Mawlood, Sawar I.; Ismaeil, Abdulilah S. (Sulaimani Journal for Pure and Applied Sciences, 2012)
The effect of oil, ethanol and total alkaloids extracted from the seeds of Nigella sativa L. (Ranunculaceae) by three different methods (soxhlet, solvent extraction, and reflux techniques) on the growth of Staphylococcus aureus was evaluated. Five concentrations (100 µl, 130 µl, 150 µl, 170 µl, 200 µl) of these extracts were utilized. The ethanol and alkaloid extracts performed better antibacterial activities than others, whereas oil extracts showed good activities only in high concentrations. Most of data of extracts showed dose dependent antibacterial effects. This study presents that solvent extraction method was the best method of extraction as it recorded better action on the growth of Staphylococcus aureus